Organizational Citizenship Behaviour, Job Satisfaction And Commitment Among Pantai Medical Centre Employee - Sin, Ku Kai (2009)
The research paper examines the impact of organizational citizenship behavior on employees' job satisfaction and commitment to the Pantai Medical Centre, Malaysia.